Urbanistikos mokslo ir studijų vietos Lietuvos klasifikatoriuose paradoksai - Daunora, Zigmas J. (Journal of Architecture and Urbanism, 2008)
Paradoxes of positioning urban science and education in the Lithuanian classificatorsUrban Design and Planning, being a significant field of architect’s professional activity, science and education, in the Lithuanian classificators of science (1998) and education (2001) is replaced by Land Management which is concerned with another field closely related to engineering management of rural territories. The paper discusses diferences in the conception of these disciplines, and need of correcting the classificators is suggested with intention to create reasonable development conditions for the science and education of urban design and planning corresponding to those existing in the other EU countries. Some of the conceptions and incorrectly used concepts of the Law on Territory Planning requiring changes are indicated.It is stated that during 11–19 years an inadequate approach to a complex and socially urgent matter, related with culture, science and art, has brought the urban development of the country to a situation having evident attributes of chaos. Most damage is done to the architecture of towns, where the role of urban design activity, defining the conceptions of built-up morphostructure, urban complexes and the architecture of public spaces, is essential. Sustainable compositional development of a town defining its individual image and aesthetic attraction also depends on the qualification of a participating architect urbanist and his role in a team of planners. A model of positioning urban design and planning in the systematic conception of architect’s professional activity, science and education as well as possibilities of supplementing the classificators are proposed.Article in Lithuanian.Santrauka. Lietuvoje priimtuose mokslo (1998 m.) ir studijų (2001 m.) klasifikatoriuose reikšmingos architekto profesinės veiklos, mokslo ir studijų kryptys – urbanistinis projektavimas ir planavimas (Town and Country Planning) – pakeistos į kraštotvarką (Land Management) – kitos srities dalyką, artimą inžinerinio kaimo teritorijų tvarkymo vadybai. Straipsnyje nagrinėjami šių disciplinų sampratos skirtumai ir iškeliama klasifikatorių tikslinimo reikmė, siekiant atkurti urbanistikos mokslui ir studijoms priimtinas plėtojimo sąlygas, adekvačias egzistuojančioms kitose ES šalyse. Nurodomos su tuo susijusios kai kurios keistinos Teritorijų planavimo įstatymo nuostatos, pateikiamas urbanistikos vietos architekto profesinės veiklos, mokslo bei studijų sisteminėje sampratoje modelis ir klasifikatorių papildymo galimybės.Reikšminiai žodžiai: urbanistinis projektavimas, urbanistinis planavimas, mokslas, studijos, klasifikacija, terminologija.First Published Online: 22 May 2013